10 years of experience in adopting, implementing and evaluating progress testing for Saudi medical students. Issue 1 (February 2023) - Alamro, Ahmad S.; Alghasham, Abdullah A.; Al-Shobaili, Hani A.; Alhomaidan, Homaidan T.; Salem, Tarek A.; Wadi, Majed M.; Saleh, Mohamed N.
الملخص: الأهداف: اختبار التقدم (أو ما يعرف بالاختبار التحصيلي) هو اختبار شامل مصمم لمطابقة اكتساب المعرفة اللازمة عند التخرج. يراقب هذا الاختبار التقدم خلال الفترة الكاملة لبرنامج البكالوريوس. بدأت كلية الطب بالقصيم بتصميم وتبني هذا الاختبار الذي يشارك فيه كليات الطب على مستوى في المملكة العربية السعودية. هدفت الدراسة الحالية إلى تحديد ما إذا كان يمكن استخدام هذا الاختبار لتقييم تقدم طلاب الطب في كليات الطب السعودية المختلفة بمقاربات تعليمية مختلفة، وكذلك ما إذا كان اعتماد طريقة الاختبار هذه ستقبله الكليات المختلفة. الأساليب: إلى جانب إنشاء اللجنة الخاصة بالاختبار، تم وضع مخطط شامل لأخذ 200 سؤال من أسئلة الاختبار من من تخصصات مختلفة. الاختبار عبارة عن اختبار كتابي في أربع ساعات. جميع عناصر الأسئلة فيه عبارة عن أسئلة ذات خيارات متعددة مبنية على سيناريو. النتائج: تم إجراء 13 جولة من اختبار التقدم. ارتفع عدد الكليات المشاركة من ثلاث كليات (285 طالبًا) في الاختبار الأول (مايو 2012) إلى أكثر من كلية20 (أكثر من 6000 طالب) من الجولة التاسعة (فبراير 2017). تراوح متوسط درجات طلاب السنة الأولى من 3.0٪ إلى 7.9٪ ، بينما تراوحت درجات طلاب السنة الخامسة من 34.0٪ إلى 43.0٪. الاستنتاج: يعتبر إجراء هذا الاختبار المصمم بدقة لتقييم التحصيل المعرفي عند التخرج من الطب تجربة مثمرة ؛ لقد ساعد في تقديم ملاحظات بناءة للمتقدمين للاختبار وأصحاب المصلحة الآخرين على المستوى الوطني. Abstract: Objectives: The progress test (PT) is a comprehensive examination that is designed to match the knowledge acquisition necessary at graduation and monitors progress during the entire period of an undergraduate program. Qassim College of Medicine (QCM) began using the multi-institutional PT in the Kingdom of Saudi Arabia (KSA). This study aimed to determine if the PT can be utilized to assess the progress of medical students at different Saudi medical colleges with different educational approaches, as well as whether this testing modality could be accepted by other colleges. Methods: Beside the establishment of a PT committee, comprehensive blueprinting was crafted to sample 200 A-type multiple choice questions (MCQs) from different disciplines. The PT is a paper-and-pencil model and is answered in a 4-h period. All PT items followed a uniform design. Results: In total, 13 rounds of the progress test have been conducted. The number of participating colleges increased from three (with 285 students) in the first test (May 2012) to more than 20 (with >6000 students) in the ninth round (February 2017). The average % scores for first-year students ranged from 3.0% to 7.9% while the average scores for fifth-year students ranged from 34.0% to 43.0%. Conclusion: The conduction of this meticulously crafted test to evaluate knowledge achievement at medical graduation is a fruitful tool and helps to provide constructive feedback for test-takers and other stakeholders relating to their relative positions among other fellows at the national level.